Analisis Pengaruh Fatwa DSN-MUI No. 83 Tahun 2023 Terhadap Pola Konsumsi Masyarakat di Kota Padang - IIlham Supriadi; Rahma Dani (JOURNAL EQUITABLE, 2024)
About how the effects of the release of Fatwa DSN-MUI No. 83 in 2023 to the people of the plains city that occurred in the field of response of the people prefer to follow the rules and the people also changed consumption patterns from those who intially used common produtcs to switch equipment to other such research and natural observastion. From the data already collected on how fatwa rules have been released one people’s consumption patterns it has been evident that some of the data gathered there are 97 of the 100 people from the country’s population that are gathered in that people agree that people support and they change their consumption patterns by switching to other inexpensive and accessible products but not impossible. There are only a number of responses and societies disapprove of the fatwa because it is not given a description of alternatif solutions or pathways to replace products or brand that are used in everyday public consumption.